PERBANDINGAN KONSEP PERSALAMAN “TERIMA KASIH” DALAM BAHASA INDONESIA DAN BAHASA JEPANG - Elizabeth Ika Hesti Aprilia Nindia Rini (IZUMI, 2014)
Abstract Greetings is necessary in human relationship. If we can’t express greeting properly we will be regarded as the less civilized. And not to know how to use expressions that show gratitude can lead us to misunderstandings that would be not good for the relationship that has been existed. Indonesian expressed gratitude by using idiomatic expressions such as”terima kasih”, “makasih”, “trims” with sincerity, meanwhile Japanese expressed kansha (gratitude) using standard existing idiomatic expressions such as “arigatou gozaimasu”, “sumimasen”, “doumo”, etc, describing the facts that occurred, describing the feeling of the speaker, and gestures. Kata Kunci : greetings, gratitude, terima kasih,arigatou gozaimasu